Management solutions in field impacts of flood and erosion on environmental pollution - Jalali, Saeid; Ghanbari, Saeed; Mohammadi, Mohammad Javad (International Journal of Education and Cognitive Sciences, 2022)
Backgrounds and Objectives: According to statistics prepared by the United Nations have entered most losses and damage to human societies among the natural disasters, floods and storm. Since the floods every year are causing loss significant of life and financial, the main aims of planning in this area are flood control and mitigation. The aim of this study is to instigate the effects of flooding and erosion on environmental pollution management options in this field.Materials and Methods: In this review study, the literature was done from 2000 to 2020 in various databases, including Medline, Web of Sciences (WOS), Google Scholar and Scopus. Data’s was collected based on available reviewed articles. The Expanded Disability Status Scale (EDSS) was evaluated for effectiveness and the effects of the studies were evaluated for safety. After processing and modification on the basis of data collected, estimated the effects of flooding and erosion.Results: The environmental impact caused changes in watershed physical, changes in shape and topography of the area influence erosion and brought in sediment, soil erosion; change the biological characteristics of water. The main effects of this including the water borne diseases such as typhoid, cholera, and create the appropriate environment for the growth of hosts and vectors of some diseases such as Schistosoma, MalariaConclusion: Finally, the findings of this study showed that the pollution due to by flood can be caused toxic acceptor waters, high PH of this water and reducing dissolved oxygen.